Meta-analisis Literasi Digital pada Pembelajaran - Indah Wigati; Weni Lestari; Moh Ismail Sholeh; Nurlaela Nurlaela; Yuniar Yuniar (Orbital: Jurnal Pendidikan Kimia, 2023)
Digital literacy has a significant role in the learning process. Several articles reveal that the use of digital literacy can improve the quality and results of learning. The search for the extent to which digital literacy influences learning can be analyzed by meta-analysis. This study aims to analyze digital literacy articles on learning that are published in national journals indexed sinta 1-6. The research design used is meta-analysis. The research sample is 16 digital literacy articles on learning which are published nationally and meet the sample selection criteria. The research data was obtained from an analysis of digital literacy articles in learning. The data were analyzed by looking at the effect size of each article based on the results of the t-test analysis. The results of the study show that the average effect size is 0.373 in the large effect category which states that digital literacy has a large influence on learning. The region with the most use of digital literacy in learning is the island of Java. Digital literacy has been widely tested on learning outcome variables and has a positive influence. So it can be concluded that digital literacy affects the learning process.